PELAKSANAAN PERJANJIAN KREDIT PEMILIKAN RUMAH PADA PT (PERSERO) BANK TABUNGAN NEGARA, Tbk. DI KOTA DENPASAR - Adi Wardani, Luh Ayu; Wiryawan, I Wayan; Rudy, Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014)
The increasing living standart of the society result on the increasing needs that must be fulfilled, meanwhile chances used by developers in a form of corporation with banking institutions offer facilities for fulfilling people’s needs for housing. Hence, PT.(Persero) Bank Tabungan Negara,Tbk (BTN) provides facilities of credits for houses with requirements and certain periods so that they can help people for having houses. The fact, however, is that there are many credit debtors of house ownership have not fulfilled their obligation as determined as agreed with BTN. The condition makes the bank difficult to develop its business in providing credits for other credit debtors so that the effort to succeed the government program on preparing housing for low standard of people become difficult.
Keywords: credits for houses